2022
DOI: 10.3390/children9081264
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Minimally Invasive Surgery—A Bibliometric Study on 30 Years of Research Activity

Abstract: Background: Pediatric minimally invasive surgery (MIS) is a standard technique worldwide. We aimed to analyze the research activity in this field. Methods: Articles on pediatric MIS (1991–2020) were analyzed from the Web of Science™ for the total number of publications, citations, journals, and impact factors (IF). Of these, the 50 most cited publications were evaluated in detail and classified according to the level of evidence (i.e., study design) and topic (i.e., surgical procedure). Results: In total, 4464… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 71 publications
0
13
0
Order By: Relevance
“…Bibliometric analysis is a crucial tool for identifying and predicting emerging trends in potential topics, which has been widely used to evaluate the literature on pediatric diseases [18][19][20][21][22]. However, there is a lack of bibliometric research on CBD.…”
Section: Discussionmentioning
confidence: 99%
“…Bibliometric analysis is a crucial tool for identifying and predicting emerging trends in potential topics, which has been widely used to evaluate the literature on pediatric diseases [18][19][20][21][22]. However, there is a lack of bibliometric research on CBD.…”
Section: Discussionmentioning
confidence: 99%
“…The lower the impact index, the higher the citation rate since publication, which indicates an augmented recognition in the scientific community. 9,12…”
Section: Data Extractionmentioning
confidence: 99%
“…In contrast to traditional bibliometric studies that provide insights into a global research productivity by using mathematical and statistical methods, none of the established measurements such as the date and journal of publication, number of citations, impact factor, impact index, or h-index are taken into account for the calculation of AAS. [7][8][9] The correlation between AAS ratings and traditional bibliometric analyses remains controversial and has not been evaluated for manuscripts with the highest AAS scores in pediatric surgery. 10 Therefore, this study aimed to identify and characterize the top 100 articles with the highest AAS in pediatric surgery.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It enables researchers to identify classical ar-ticles from a great number of publications, which can promote the development in special research areas. Traditionally, measures of bibliometrics are the mainstream for assessing the influence of article and journal performance, which have been widely used and accepted by researchers [1,2]. However, studies have shown that it takes up to 3 years after publication for a certain article to reach citation peak and this delayed period affects the judgement of including Twitter, Blogs, Facebook and others are providing novel insights into the immediate impact of research work com-pared to traditional bibliometrics.…”
Section: Introductionmentioning
confidence: 99%